Treating dementia : do we have a pill for it? - Ballenger, Jesse F. (Baltimore : Johns Hopkins University Press, 2009)
"Treatment for age-related dementia and the growing reliance on pharmaceuticals to alleviate its worst symptoms raise a number of questions about attitudes toward aging and cognition, the relationship between growing older and getting sick, and the conflicting interests of patients, caregivers, physicians, scientists, and business. This volume aims to foster a constructive debate about the future of dementia treatment by providing multiple perspectives on these tangled issues."--BOOK JACKET.
The classification of Alzheimer's disease and mild cognitive impairment : enriching therapeutic models through moral imagination / Danny George and Peter J. Whitehouse -- Notes toward a future history of treatments for cognitive failure / David Healy -- Alzheimer's disease : pathogenesis, models, and experimental therapeutics / Donald L. Price ... [et al.] -- From the periphery to the center : treating noncognitive, especially behavioral and psychological, symptoms of dementia / Annette Leibing -- Pharmacologic treatment of dementia : a clinician's view / Alan A. Anderson -- Managing Dad / Judith Levine -- Making sense of the language of benefit for Alzheimer's disease treatments / Jason H.T. Karlawish -- Science and marketing : the promotion of donepezil in the primary research literature / John R. Gilstad and Thomas E. Finucane -- Profiling drugs and diseases : the shaping, making, and marketing of drugs for Alzheimer's disease / Rein Vos -- Can we fix this with a pill? : qualities of life and the aging brain / Peter J. Whitehouse -- Necessary inventions : antidementia drugs and heightened expectations for aging in modern American culture and society / Jesse F. Ballenger -- Truth and hope in drug development and evaluation in Alzheimer's disease / Tiago Moreira -- APOE genotyping, risk estimates, and public understanding of susceptibility genes / Margaret Lock and Adam Hedgecoe -- Developing drugs for dementia : hope, hype, and hypocrisy / Peter V. Rabins.
Includes bibliographical references and index.
Keywords: Dementia -- Chemotherapy; Alzheimer Disease -- drug therapy; Alzheimer Vaccines -- economics; Alzheimer Vaccines -- therapeutic use; Drug Discovery -- ethics; Marketing -- ethics